2022
DOI: 10.14715/cmb/2022.68.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic (Allium sativum) - supplemented diet on growth performance, body composition and fatty acid profile of rainbow trout (Oncorhynchus mykiss)

Abstract: In this study, rainbow trout were fed for a total of 90 days with different feed mixes containing 0.00%, 1.00%, 1.50% and 2.00% garlic (Allium sativum). The effect of garlic on the growth performance, body composition and fatty acid profile of rainbow trout was researched. The starting weight of fish in the experimental group was approximately 64.12±0.29 gr, which increased to 234.12±3.54gr, 246.31±4.41gr, 258.74±4.42gr, and 268.79±4.79gr, while the difference in growth between the groups was observed to be st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
4
8
0
Order By: Relevance
“…The application of phytase enzyme and dietary inorganic phosphate led to significant improvement in economic conversion ratio and EPI in the present study. In line with Dikel et al (2010) and Öz et al (2018), our results revealed that dietary supplementation of phytase as a growth promoting agent significantly lowered the ECR. ECR was significantly low in fish fed on diets supplemented with phytase, leading to significantly high EPI, which was the highest in fish fed on diet T4 (750 OTU/kg) in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The application of phytase enzyme and dietary inorganic phosphate led to significant improvement in economic conversion ratio and EPI in the present study. In line with Dikel et al (2010) and Öz et al (2018), our results revealed that dietary supplementation of phytase as a growth promoting agent significantly lowered the ECR. ECR was significantly low in fish fed on diets supplemented with phytase, leading to significantly high EPI, which was the highest in fish fed on diet T4 (750 OTU/kg) in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Investigation of body proximate composition of rainbow trout which were fed with different levels of nettle and tarragon powder, showed the highest and the least percent of moisture in fish fed on N1+T1 and N3 respectively. In previous studies, garlic powder and black cumin oil (Nigella sativa) reduced body proximate moisture in rainbow trout (Öz et al, 2018), brown trout (S. caspius) (Zaefarian et al, 2017) and demonstrated high moisture in control (Öz et al, 2018;Zaefarian et al, 2017) similar to our result. Another study showed the highest level of moisture in control and the least level of moisture in sterlet sturgeon which was fed with garlic powder (Lee et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the highest body proximate protein was detected in fish fed on N3. In this line, the inclusion of garlic powder (Zaefarian et al, 2017), green tea ethanol extract (Hwang et al, 2013) and black cumin oil ( Nigella sativa ) (Öz et al, 2018) increased body protein in brown trout ( S. caspius ), black rockfish ( S. schlegeli ) and rainbow trout respectively. Furthermore, garlic powder and oil increased body proximate protein and reduced fat in Nile tilapia ( Oreochromis niloticus ) (Metwally, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this rich content, pharmacological properties are also quite high in black cumin oil. Its most known properties are antibacterial, antifungal, antiviral, antiprotozoan, antihistamine, antioxidant, non‐inflammatory, and immunostimulating properties (Altinterim, 2010; Öz, Dikel, & Durmus, 2018; Öz, Inanan, & Dikel, 2018). The content and pharmacological properties of black cumin oil stimulate growth in fish, reduce resistance to diseases and increase the appetite of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Black cumin oil used in the experiment was obtained from a commercial company and produced by cold press. In the study, only 1% black seed oil was supplemented to G2 and G4 feeds and the rate of black seed oil to be added to the feed was determined according to Öz, Dikel, & Durmus, 2018.…”
Section: Methodsmentioning
confidence: 99%